JUMBO Film as a Turning Point for Indonesian Animated Films in the Digital Era - Tuty Mutiah; Bonardo Marulitua A; Ken Norton Hutasoit; Ali Imron Hamid; Syarif Fitri (Program Studi Pendidikan Bahasa Inggris, Universitas Pendidikan Muhammadiyah Sorong, 2025)
The Indonesian film industry has shown significant development in recent years, particularly in terms of genre diversification and technical quality. One major achievement in this sector is the success of the animated film JUMBO (2025), which became the third highest-grossing Indonesian film of all time, with over 7 million viewers. This success reflects a major shift in Indonesian audience preferences toward local animated films, which were previously often considered less popular. JUMBO not only offers entertainment but also presents a strong and emotional narrative, along with relevant Indonesian social and cultural values. This study aims to examine JUMBO as a manifestation of a new paradigm in Indonesian cinema, focusing on its narrative approach, technical and visual aspects, as well as the digital communication strategies used to market the film. In addition, audience responses to the film are analyzed to understand its impact on public perception of local animated films. The research uses a qualitative approach, including content analysis of the film and a study of social media use in its marketing strategy. JUMBO not only provides visual entertainment but also conveys universal values such as struggle, family, and hope, making it both relevant and emotionally resonant for viewers. The findings show that JUMBO has successfully reshaped audience expectations regarding the quality of local films and opened new opportunities for the development of the animation genre in Indonesia. The film’s success highlights the great potential for the Indonesian animated film industry to grow further and be embraced by both local and international audiences.